A single-leg standing test evaluation system for fall prevention in workers. (17th December 2022) - Mikami, Hayato; Sakata, Mami; Shima, Keisuke; Nagara, Tomoyuki; Yamashita, Makiko; Shimatani, Koji
Abstract : This paper developed a simple and quantitative evaluation system for a single-leg standing test. The proposed method represents the stand-up motion as a state transition model by quantitative measurement using a camera with a depth sensor (Azure Kinect) and a force plate. It objectively evaluates the movement of each state. In the experiment using the prototype, the evaluation results by the system and the skilled athletic trainer were the same for all subjects, and the shape of the radar chart was different among the subjects whose evaluation scores were the same. The results show that the proposed system can be quantitative evaluation even at worksites without skilled evaluators. GRAPHICAL ABSTRACT: UF0001